Can audience involvement stimulate visit intention in Chinese Kung Fu? Using a serial multiple mediation model to explore film tourism - Xia, Jiangtao; Qiu, Qihang; Zuo, Yifan; Wang, Liang (Frontiers in Psychology, 2022)
The popularity of film and television causes audiences to flock to the location of filming, and thus film tourism is widely been used as an efficient tool in destination branding and marketing. Accordingly, this study takes Chinese Kung Fu film and television as an example, using the method of regression model to study audience involvement, cognitive destination image, and tourists’ anticipated experiences and visit intention into an overall framework. Findings illustrate a significant positive correlation among audience involvement, visit intention, cognitive destination image, and tourists' anticipated experiences. At the same time, cognitive destination image and tourists' anticipated experiences have a partial mediating effect on the relationship between audience involvement and cognitive destination image, which play multiple mediating roles. This study provides three suggestions for the development of film tourism, namely maximizing the marketing effect, strengthening the unity of film and images of destinations, and making full use of modern marketing tools.